Research on optimization of crude oil transportation development system in the Yangtze River based on transportation capacity regulation. Issue 2 (February 2019) - Lei, Jiang; Yi, Luo
Abstract: Based on the Yangtze River macroeconomic regulation and control of hazardous cargo transportation market background, the article analyzes the economic and trade situation and policy environment of the crude oil transportation market in view of the contradiction between supply and demand of crude oil transportation in the Yangtze River, and analyses the future supply and demand development trend of the transportation capacity, puts forward the optimization of development plan and related recommendations for the Yangtze River inland crude oil transportation system.